매체혼탁에 따른 파장가변 빛간섭단층촬영과 스펙트럼영역 빛간섭단층촬영 영상의 질 비교 - 홍은희(Eun Hee Hong); 박승훈(Seung Hun Park); 이정욱(Jung Wook Lee); 이주향(Ju Hyang Lee); 송인석(In Seok Song); 이병로(Byung Ro Lee) (Daihan angwa haghoi jabji, 2016)
목적: 안구 매체혼탁이 있는 안에서 파장가변 빛간섭단층촬영(swept-source optical coherence tomography, SS-OCT)과 스펙트럼영역 빛간섭단층촬영(spectral domain optical coherence tomography, SD-OCT) 영상의 질을 비교하고자 하였다. 대상과 방법: 정상 40안, 매체혼탁 60안(백내장 30안, 유리체혼탁 20안, 각막혼탁 10안)에서 SS-OCT와 SD-OCT의 6×6 macular scan을 시행하였다. 각 영상에 대해 영상의 질의 객관적 지표로 quality factor (QF)를, 주관적 지표로 subjective grading scale (SGS)을 측정하여 정상안과 매체혼탁안에서의 영상의 질 차이를 비교하고 매체혼탁의 종류와 정도에 따른 영상의 질 차이를 비교하였다. 결과: 정상안과 매체혼탁안 모두에서 SD-OCT에 비해 SS-OCT에서 객관적 지표, 주관적 지표 모두 더 높은 영상의 질을 보였다(p＜0.001). SS-OCT와 SD-OCT의 영상의 질 차이는 매체혼탁의 종류에 따른 유의한 차이는 없었고(QF: p=0.188, SGS: p=0.635), SD-OCT QF를 기준으로 매체혼탁의 정도에 따라 분류한 두 군(Group I: 20≤QF＜50, II: 0≤QF＜20) 간의 비교에서도 유의한 차이는 보이지 않았다(QF: p=0.088, SGS: p=0.051). 결론: SS-OCT는 매체혼탁의 종류나 정도에 관계없이 SD-OCT에 비해 개선된 영상의 질을 보여주며, 이는 매체혼탁안에서 정확한 질병 진단 및 경과 평가에 도움이 될 것으로 여겨진다. Purpose: To compare the image quality between swept-source optical coherence tomography (SS-OCT) and spectral domain optical coherence tomography (SD-OCT), especially in eyes with media opacity. Methods: Forty eyes without media opacity and 60 eyes with media opacity (30 eyes with cataract, 20 eyes with vitreous opacity, and 10 eyes with corneal opacity) were included in this study. SD-OCT and SS-OCT 6 × 6 macular scans were taken by a single operator. For image quality analysis, a total of 200 OCT images were subjectively graded by two trained retina specialists and measured quantitatively using the image quality factor (QF) built into the OCT devices. Results: Compared to conventional SD-OCT, SS-OCT had statistically significantly better subjective and objective grades in the normal group, as well as each of the media opacity groups (p-value < 0.001). In both the subjective and objective grades, there was no significant difference according to the types of media opacity (QF: p = 0.188, subject grading scale [SGS]: p = 0.635) and the degree of media opacity (Group I: 20 ≤ QF < 50, Group II: 0 ≤ QF < 20; QF: p = 0.088, SGS: p = 0.051) in the superiority of image quality of SS-OCT to SD-OCT. Conclusions: In this media opacity patient population, swept-source OCT is a superior diagnostic tool when compared with SD-OCT in both objective and subjective assessments, even in the ocular media opacity. This result may be useful in diagnosis and progression detection of retinal disease in media opacity eyes. KCI Citation Count: 0